(untitled) (Journal of Engineering, 2009)
The aim of reducing drag is to increase the flow efficiency by using the same pipes and pumps. As a result the amount of crude oil transported will increase without using new pipes and pumps. In the present work, the effectiveness of two surfactants (Sodium dodecyl benzene sulfonate (SDBS) and Sodium lauryl sulfate (SLS)) are studied by using a closed loop system. This system consists of three pipes made from commercial steel, each one with different diameter (0.75, 1 and 1.5 inch). The length of each individual test section of the pipe is two meters. The experimental work is achieved under three different temperatures (30º, 40º and 50°C). The concentrations of both surfactants used are ranging between 50 to 300 weight ppm. Laboratory tests showed that there is a direct proportionality between the percentage of drag reduction (%DR) on one hand and in Reynolds number and pipe diameter on the other hand. Inverse proportionality is observed between %DR and temperature. The %DR increases as concentration increases, but at a certain higher concentration, this relation will reverse. The final results showed that the highest drag reduction (%DR) was 23.67%. This value is obtained when 200 ppm SDBS is added at 30°C. The calculated values of friction factor were found to be situated between Blasius and Virk asymptote adjacent.